2011
DOI: 10.1007/s11604-010-0520-3
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of multidetector computed tomography for patients with suspected scaphoid fractures and negative radiographic examinations

Abstract: MDCT offers highly accurate results, especially concerning cortical involvement, and is a useful alternative in facilities lacking MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 16 publications
0
29
0
7
Order By: Relevance
“…These results did not change on sensitivity analysis with the four ED-based studies with LR+ of 23.0 (95% CI = 7.8 to 68) and LR-of 0.18 (95% CI = 0.16 to 0.34). 37,40,77,92 Ilica et al 90 used MRI exclusively as the criterion standard, but estimates of diagnostic accuracy did not differ from other studies using clinical examination, follow-up x-ray, or CT as the criterion standard. All of the studies except for one were prospective study designs, so sensitivity analysis was not conducted based on study design.…”
Section: Ctmentioning
confidence: 85%
See 3 more Smart Citations
“…These results did not change on sensitivity analysis with the four ED-based studies with LR+ of 23.0 (95% CI = 7.8 to 68) and LR-of 0.18 (95% CI = 0.16 to 0.34). 37,40,77,92 Ilica et al 90 used MRI exclusively as the criterion standard, but estimates of diagnostic accuracy did not differ from other studies using clinical examination, follow-up x-ray, or CT as the criterion standard. All of the studies except for one were prospective study designs, so sensitivity analysis was not conducted based on study design.…”
Section: Ctmentioning
confidence: 85%
“…37,40,77,[88][89][90][91][92] The criterion standard reported varied significantly and included clinical follow-up up to 16 months, 77,92 6-week x-ray, 37,89,91 bone scan, 40 and MRI. 90 The timing of the CT relative to the injury varied from less than 1 day, 37,40,89 to within 4 days, 77,88,91 or 1 week. 90,92 The older studies reported using four-row spiral CTs (120-KV, 100-mA, and 1.5-second scan time with 1.0-to 1.2-mm slices, pitch 3.5, Figure 11.…”
Section: Ctmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of true fracture among suspected scaphoid fracture was derived from studies that prospectively or consecutively recruited at least 50 patients with suspected scaphoid fractures and confirmed scaphoid fracture with MRI or radiographs with follow-up of at least 6 weeks. 4,6,[14][15][16][17][18][19][20][21][22] The weighted mean (the numbers of patients with a clinical condition reported in different studies were summed and then divided by the sum of the total number of patients in each study) was used as the baseline value, and the range obtained from these studies was used for the sensitivity analysis. One prospective study provided the probability of positive clinical signs of patients with suspected scaphoid fracture at 2 weeks after injury.…”
Section: Strategy 6 (Day 3 Mri) and Strategy 7 (Day 3 Bone Scan)mentioning
confidence: 99%